Assessment of perceived quality: comparison of sports apparel retail chains - Gomes, J.; Martins, A.; Ferreira, J. (International Journal of Management and Applied Science, 2018)
Sports apparel retail is a very competitive industry in Portugal and is dominated by two main players that continuously seek to capture more customers. The quality of the service provided is a key issue for a company to succeed in the market. Although service quality has been explored in literature, its link to the value proposition of the retail stores is still missing. This research aims at analyzing the adequacy of the service provided by each of these main players to customers’ desires in a comparative way. Customers’ perceived quality is assessed as well as suitability of companies’ desired benefits for the customers. Data was collected using interviews and a customer questionnaire. A sample of 423 responses is used. Conclusions showed that Decathlon has a better fit to customers’ desires as well as better perceived quality than Sports Zone. Specific managerial recommendations for the improvement of the service quality are provided for both companies.